Forward guidance and its effectiveness: A macro finance shadow-rate framework - Junko Koeda; Bin Wei (Federal Reserve Bank of Atlanta, 2023)
Forward guidance provides monetary policy communication for an economy at the effective lower bound (ELB). In this paper, we consider both calendar- and outcome-based forward guidance about the timing of liftoff. We develop a novel macro-finance shadow rate term structure model by introducing unspanned macro factors and an outcome-based liftoff condition. We estimate the model using the maximum likelihood method with extended Kalman filter. Based on the estimation results, we show that outcome-based forward guidance is indeed effective and has significant monetary-easing effects on the real economy in both ELB periods of the global financial crisis (GFC) and the COVID-19 pandemic. In particular, we find that the overall impact on the unemployment rate is about 0.8 percent during both the GFC and the pandemic, but outcome-based forward guidance contributes more in the former than in the latter ELB period (about 0.30 percent versus 0.15 percent).
Keywords: E43; E44; E52; E58; 330; forward guidance; effective lower bound (ELB); liftoff; term structure; shadow rate; macro finance; unspanned macro factors